Lean in the Aspect of Sustainability - Pető, Orsolya (Theory, Methodology, Practice – Review of Business and Management, 2012)
The article introduces the principles of Lean and Sustainability. It will analyze the points where overlaps occur between these two fields and show how a well-functioning unified system focusing on both areas could be developed. It looks at the effects of Lean and its -best-known tool 5S on the pillars of Social, Economical and Environmental Sustainability. Finally, it makes proposals on how to develop a sustainable system and what could be applied.